Visit Of Ante Natal Care Reviewed From The Attitude And Support Of Health Workers At Tanjung Makmur Health Center, Ogan Komering Ulu Regency - Anggrawati Wulandari; Lilis Suryani (Journal for Quality in Public Health, 2025)
Antenatal Care (ANC) that is less than the target is a problem that needs to be solved, one of which is because of attitudes and support that are not yet optimal. The purpose of this study was to determine the relationship between attitudes and support from health workers and the coverage of antenatal care (ANC) visits in the Tanjung Makmur Health Center working area in 2023. This study used a cross-sectional approach. The sampling technique used total sampling with a sample size of 35 pregnant women and data collection was carried out using a questionnaire. The results showed that most pregnant women's attitudes towards ANC visits had a negative attitude of 22 respondents (62.9%), p-value = 0.001 (p <0.05), and 19 respondents (54.3%) stated that health workers did not support, p-value = 0.012 (p <0.05). There is a relationship between maternal attitudes and support from health workers and the coverage of ANC visits. It is hoped that pregnant women will care more about maternal and child health by carrying out ANC examinations properly and completely.